Unconventional warfare in South Asia shadow warriors and counterinsurgency - Gates, Scott; Roy, Kaushik (Ashgate Publishing Company, 2014)
Framing the debate using case studies from across South Asia as well as China, Afghanistan and Burma and using a wealth of primary and secondary sources, this book takes a closer look at the organization and doctrines of the 'shadow armies' and the government forces which fight the former.